2014
DOI: 10.4142/jvs.2014.15.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Dietary germanium biotite supplementation enhances the induction of antibody responses to foot-and-mouth disease virus vaccine in pigs

Abstract: We evaluated the potential ability of germanium biotite (GB) to stimulate the production of antibodies specific for foot-and-mouth disease virus (FMDV). To this aim, we measured the total FMDV-specific antibody responses and IgM production after vaccination against FMD both experimentally and in the field. GB supplementation with FMDV vaccination stimulated the production of anti-FMDV antibodies, and effectively increased IFN-γ and TNF-α levels. These results suggest that GB may be a novel alternative feed sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 9 publications
2
9
0
Order By: Relevance
“…These results implied that dietary supplementation of BBM mainly stimulated Th 1-specific responses, which include increased IFN-γ production. We reported similar results in our previous study, which showed an increase in the level of CD4 + T lymphocytes and IFN-γ after administration of a biotite-supplemented diet [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…These results implied that dietary supplementation of BBM mainly stimulated Th 1-specific responses, which include increased IFN-γ production. We reported similar results in our previous study, which showed an increase in the level of CD4 + T lymphocytes and IFN-γ after administration of a biotite-supplemented diet [ 13 ].…”
Section: Discussionsupporting
confidence: 88%
“…by stimulating lysozyme activity. Our previous studies also reported strong stimulation of secretion after administration of a biotite-supplemented diet CD4 + T lymphocytes and IFN-γ [ 8 , 13 ].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The anti-FMDV serotype O antibody level of each serum sample was determined using a PrioCHECK FMDV type O ELISA kit (Prionics, Switzerland). A protocol of blocking the enzyme-linked immunosorbent assay (ELISA) to detect antibodies against FMDV serotype O was employed according to the manufacturer's instructions as previously described [ 6 ]. Briefly, fresh serum was separated by centrifugation at 2,000 × g for 10 min at 4℃.…”
mentioning
confidence: 99%
“…In addition, a recent report suggested that germanium biotite (GB), which is a novel alternative feed supplement, could play a role as an immunostimulator of boosting agent for improving the efficacy of FMDV vaccine in conventional 8-week old pigs. A commercially available high potency double oil-based vaccine contained at least 6 PD 50 per dose of inactivated O 1 Manisa FMD virus [ 6 ]. Thus, our study was conducted in 8-week-old growing pigs pre-treated with 60 mg of poly-γ-glutamic acid (γ-PGA) 3 days before vaccination.…”
mentioning
confidence: 99%